Spin-orbit coupling in manganese doped calcium molybdato-tungstates. Issue 3 (15th February 2018) - Groń, T.; Pawlikowska, M.; Tomaszewicz, E.; Oboz, M.; Sawicki, B.; Duda, H.
Abstract: The manganese doped calcium molybdato-tungstates with the formula of Ca1- x Mn x (MoO4 )0.50 (WO4 )0.50 ( x = 0.01, 0.03, 0.05, 0.10, 0.125, and 0.15) were successfully obtained by two-step synthesis using in both steps a solid state reaction route. All ceramics show scheelite-type tetragonal structure with space group I4 1 /a . The electrical and magnetic studies within the temperature range of 2–300 K showed a weak p -type electrical conductivity and the paramagnetic state of Mn-doped ceramic materials. With increasing Mn content in samples under study, a change in the short-range interactions from ferromagnetic to antiferromagnetic as well as an increase in the orbital contribution to the magnetic moment, resulting in a strong spin-orbit coupling, were observed. The Brillouin procedure was used to estimate the Landé factor.